Menyelami Etika Konsumsi: Berbelanja Kebutuhan Harian pada Individu yang Mengadopsi Gaya Hidup Berkelanjutan - Laya, Sitti Monira Fyenci F (Sasdaya: Gadjah Mada Journal of Humanities, 2024)
The problem of excessive consumption and consumer egoism is pervasive in many markets. This phenomenon not only has a negative impact on the environment, but also causes social problems and the economic integrity of society. The culture of consumerism and technology influences consumption behavior, encouraging excessive purchasing and irrational consumption decisions. This research discusses consumption actions carried out by informants which are based on reducing waste and supporting local products. The method used in this research was interviews with 4 informants in Yogyakarta who live a sustainable lifestyle. The aim of this research is to provide a more specific understanding that consumption is not just an economic act, but is a complex social and cultural phenomenon that can provide a deeper picture of humans and their environment. This research aims to understand how consumers consume goods and services to create a positive impact on the environment and economy. By examining the role of technology in driving consumption, it is possible to identify areas where consumers can improve their needs and satisfaction. The research results showed that ethical consumption behavior was carried out by the informants unconsciously. This article highlights the role of individuals in influencing consumption habits and encouraging change towards more responsible consumption.